Effects of folkloric dance on depression levels of education among children at 7-11 age group - Ahmet Aydın; Mehibe Akandere (Türk Spor ve Egzersiz Dergisi)
The goal of is this study is to examine effects of folk dances as a spare time activity on depression levels of students. Pre test – final test model is applied during the study and Beck Depression Scale (11) in terms of Depression Scale of Children (DSC) as the data collection device. The study is applied on totally 500 students continuing to study in downtown of Konya, 250 as test subject and 250 as control subject. Folkloric dance exercised with the experimental group during 10 weeks and beck depression scale was applied on both test and control groups before and after the study. For determination of differences, One Way Anova test was used while Tukey test was used for the differences between groups after tests of homogeneity of variances and distribution of data and the tolerance level was measured as 0.05. In terms of evidences obtained from the study it was observed that there was a decrease at depression levels of study group and an increase at control group. A meaningful difference was observed between first and last measurement of study and control groups in terms of statistical information (P lt;0.05). A decrease at depression levels of 9-10 age students (P lt;0.05) while there was not a meaningful difference at depression levels of students in terms of gender and number of brothers/sisters (P gt;0.05). A meaningful decrease at depression levels of individuals who have mothers working at public or private sector was observed (P lt;0.05). In terms of comparison about the jobs of fathers, a decrease was observed at students who have fathers working at public or private sector while there was an increase at depression level of students who have self-employed fathers. While a meaningful decrease was observed at students who have graduate or post-graduate degree parents (P lt;0.05), there was an increase at students who have primary school graduated parents. A meaningful decrease in terms of statistics observed at students living at a family which has a high average of income (P lt;0.05). Consequently, it was observed that the exercises of folkloric dance have positive effects on depression levels, during the study held in order to examine effects of folkloric dance on depression levels of 7-11 age students.